Carbon rich media for luminescence-based surface dosimetry and study of associated surface defects - Lam, S.E. *; Bradley, D.A. *; Nawi, S.N. Mat; Khandaker, Mayeen Uddin *; Sani, S.F. A. (Elsevier, 2023)
The present study continues research into the utilisation of carbonaceous media for medical radiation dosimetry, focusing on the effects of surface area-to-volume ratio and carbon content on structural interaction alterations and dosimetric properties in sheet- and bead-type graphitic materials (with the respective carbon content of ∼98 wt% and ∼90 wt%). Using 60Co gamma-rays and doses from 0.5 Gy to 20 Gy, the study has been made of the response of commercially available graphite in the form of 0.1 mm, 0.2 mm, 0.3 mm and 0.5 mm thick sheets, also of activated carbon beads. Confocal Raman and photoluminescence spectroscopy have been employed, examining radiation-induced structural interaction alterations. Dose-dependent variation in the Raman intensity ratio ID/IG relates to the varying dominance of defect generation and dose-driven defect annealing. Of the various thickness graphite sheets, the 0.1 mm thick medium possesses the greatest surface area-to-volume ratio. Perhaps unsurprisingly, it also exhibits the greatest thermoluminescence (TL) yield compared to that of the other carbonaceous sheet foils used herein. Moreover, the second greatest mass-normalised TL yield has been observed to be that of the porous beads, reflected in the greater defect density (ID/IG > 2) when compared to the other media, due in part to their inherent feature of large internal surface area. Considering the challenge posed in matching skin thickness with skin dose, the near tissue equivalent graphite sheets show particular promise as a skin dosimeter, sensitive as a function of depth.